Strategi Efektif Menulis Artikel untuk Jurnal Terindeks Scopus: Pelatihan Meningkatkan Kualitas Publikasi Ilmiah Dosen: Pengabdian - Marthin Nanere; Conchita V. Latupapua; Restia Christianty; Pieter N. R. Rehatta; Hasmia Melati Arifin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Article writing training for Scopus indexed journals organized by the Management Department, Faculty of Economics and Business, Universitas Pattimura aims to improve lecturers' skills in writing quality scientific articles. This activity involves lecturers from three departments at the Faculty of Economics and Business, namely Management, Accounting, and Development Economics. Resource persons who are experienced in international publications provide an understanding of effective writing techniques, selecting the right journal, and strategies for dealing with a strict journal review process. Participants are taught how to write systematic articles, use clear language, and the importance of framing and collaboration in scientific writing. In addition, interactive discussions are very helpful in providing additional insights related to the challenges faced in writing for Scopus indexed journals. It is hoped that this training can improve the quality of lecturers' publications, increase opportunities to be accepted in Scopus indexed journals, and contribute to the development of science at the global level.